Island of the Blue Dolphins - O'Dell, Scott (Boston, MA : Houghton, 1960)
The story of an Indian girl who lived alone for 18 years on an island.
9-12.
4-7.
Awarded the Newbery Medal, 1961.
Keywords: Native Americans -- Fiction; Wilderness survival -- Fiction; San Nicolas Island (Calif.) -- Fiction